Equality of Educational Opportunity through the Zoning System in Senior High Schools - Ihsan, Fatoni (Jurnal Komunikasi Pendidikan, 2022)
This article to evaluate the implementation of Student Admission (PPDB) by Zoning System in achieving the vision of educational equality, a case study in the South Tambun Region. Initially, the government issued Permendikbud number 51 of 2018 regarding PPDB BY Zoning System to remove the stigma of favorite and non-favorite schools and facilitate supervision of students. This research uses a qualitative approach, then the concept from James S. Coleman through his book Equality of Educational Opportunity (1967) describes the principles and concepts of equality of educational opportunity distribution in numerous ways. Coleman's study is used to assess the availability of equality of educational opportunity for various groups of students in Indonesia through a zoning system that has a vision of social equality for the community. Based on the results of the study, the zoning system has been running procedurally. However, the goal of equality of educational opportunities is hampered by the limitation of the old value-oriented paradigm and the consequences of new inequalities.